Bond strength and morphology of enamel using self-etching adhesive systems with different acidities - Sandra Kiss Moura; Alessandra Reis; Arlete Pelizzaro; Karen Dal-Bianco; Alessandro Dourado Loguercio; Victor Elias Arana-Chavez; Rosa Helena Miranda Grande (Journal of Applied Oral Science, 2009)
OBJECTIVES: To assess the bond strength and the morphology of enamel after application of self-etching adhesive systems with different acidities. The tested hypothesis was that the performance of the self-etching adhesive systems does not vary for the studied parameters. MATERIAL AND METHODS: Composite resin (Filtek Z250) buildups were bonded to untreated (prophylaxis) and treated (bur-cut or SiC-paper) enamel surfaces of third molars after application of four self-etching and two etch-and-rinse adhesive systems (n=6/condition): Clearfil SE Bond (CSE); OptiBond Solo Plus Self-Etch (OP); AdheSe (AD); Tyrian Self Priming Etching (TY), Adper Scotchbond Multi-Purpose Plus (SBMP) and Adper Single Bond (SB). After storage in water (24 h/37°C), the bonded specimens were sectioned into sticks with 0.8 mm² cross-sectional area and the microtensile bond strength was tested at a crosshead speed of 0.5 mm/min. The mean bond strength values (MPa) were subjected to two-way ANOVA and Tukey's test (α=0.05). The etching patterns of the adhesive systems were also observed with a scanning electron microscope. RESULTS: The main factor adhesive system was statistically significant (p<0.05). The mean bond strength values (MPa) and standard deviations were: CSE (20.5±3.5), OP (11.3±2.3), AD (11.2±2.8), TY (11.1±3.0), SBMP (21.9±4.0) and SB (24.9±3.0). Different etching patterns were observed for the self-etching primers depending on the enamel treatment and the pH of the adhesive system. CONCLUSION: Although there is a tendency towards using adhesive systems with simplified application procedures, this may compromise the bonding performance of some systems to enamel, even when the prismless enamel is removed.